Biogeographic conservation of the cytosine epigenome in the globally important marine, nitrogen‐fixing cyanobacterium Trichodesmium. (2nd November 2017) - Walworth, Nathan G.; Hutchins, David A.; Dolzhenko, Egor; Lee, Michael D.; Fu, Feixue; Smith, Andrew D.; Webb, Eric A.
Summary: Cytosine methylation has been shown to regulate essential cellular processes and impact biological adaptation. Despite its evolutionary importance, only a handful of bacterial, genome‐wide cytosine studies have been conducted, with none for marine bacteria. Here, we examine the genome‐wide, C 5 ‐Methyl‐cytosine (m5C) methylome and its correlation to global transcription in the marine nitrogen‐fixing cyanobacterium Trichodesmium . We characterize genome‐wide methylation and highlight conserved motifs across three Trichodesmium isolates and two Trichodesmium metagenomes, thereby identifying highly conserved, novel genomic signatures of potential gene regulation in Trichodesmium . Certain gene bodies with the highest methylation levels correlate with lower expression levels. Several methylated motifs were highly conserved across spatiotemporally separated Trichodesmium isolates, thereby elucidating biogeographically conserved methylation potential. These motifs were also highly conserved in Trichodesmium metagenomic samples from natural populations suggesting them to be potential in situ markers of m5C methylation. Using these data, we highlight predicted roles of cytosine methylation in global cellular metabolism providing evidence for a 'core' m5C methylome spanning different ocean regions. These results provide important insights into the m5C methylation landscape and its biogeochemical implications in an important marine N2 ‐fixer, as well as advancing evolutionary theory examining methylation influences on adaptation.